2014
DOI: 10.1177/0093854814539801
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Effectiveness of Delinquency Prevention Programs

Abstract: Empirical research indicates that males are more likely than females to be delinquent, yet it is unclear why this gender gap exists. This uncertainty can impede gender-responsive prevention efforts to implement programs that target the criminogenic factors most salient for each sex. However, information from experimental evaluations of gender differences in the effectiveness of prevention services can guide gender-responsive approaches. This article provides a systematic review of such literature. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 93 publications
(84 reference statements)
0
14
0
5
Order By: Relevance
“…Analysing behaviour in the aspect of gender, it is stated that antisocial behaviour is more often demonstrated by male representatives (Hellström and Beckman, 2019). Comparing it with violence and aggression, the same trend is seen, where men are more inclined to demonstrate aggression in their behaviour than women, and this is especially true speaking about direct physical aggression (Fagan and Lindsey, 2014). On the other hand, studies show that female bullying is more often directed at females; while male bullying, both at females and males (Namie and Namie, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Analysing behaviour in the aspect of gender, it is stated that antisocial behaviour is more often demonstrated by male representatives (Hellström and Beckman, 2019). Comparing it with violence and aggression, the same trend is seen, where men are more inclined to demonstrate aggression in their behaviour than women, and this is especially true speaking about direct physical aggression (Fagan and Lindsey, 2014). On the other hand, studies show that female bullying is more often directed at females; while male bullying, both at females and males (Namie and Namie, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…For example, they may examine student survey results separately by gender to determine if males and females report different levels of risk and protective factor exposure and ensure that prevention programs address the needs of both sexes. Analyses of gender differences in the impact of community-based interventions and greater theoretical attention to differences in exposure to and salience of community influences for males and females are important as to date little such work exists (Fagan and Lindsey 2014; Zahn and Browne 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Second, there is some evidence that males and females vary in levels of and susceptibility to risk and protective factors related to problem behaviors (Fagan et al 2007; Kumpfer et al 2008), which would suggest that interventions designed to alter these factors may have differential effects by gender. Third, the impact of prevention programs has varied by gender in some evaluations, with some programs showing stronger effects for females and others showing stronger effects for males (Fagan and Lindsey 2014). Some programs have also shown harmful effects for one sex or the other, for example, increasing substance use and other behavioral health problems instead of reducing them (Sloboda et al 2009; Yin and Ware 2000).…”
Section: Gender Differences In the Impact Of Ctcmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence has suggested that prevention programs can have differential impact by gender (Blake, Amaro, Schwartz, & Flinchbaugh, 2001; Fagan & Lindsey, 2014; Foley, 2008). Prior analyses have found that CTC produced greater reductions in use of alcohol and smokeless tobacco among boys than girls by Grade 8 (Oesterle, Hawkins, Fagan, Abbott, & Catalano, 2010) and a marginally greater reduction in delinquency for boys than for girls in Grade 10 (Oesterle et al, 2014).…”
Section: Subgroup Differencesmentioning
confidence: 99%